UJI EFIKASI JAMUR ENTOMOPATOGEN Beauveria bassiana TERHADAP TINGKAT MORTALITAS LARVA NYAMUK Culex quinquefasciatus - Fitri Dewi Puspita Anggraini; Retno Hestiningsih; Lintang Dian Saraswati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2015)
Culex quinquefasciatus is a vector of filariasis bancrofti. One of preventive action that might be work is breaking the chain of transmission using biolarvicide fungus to kill the mosquito’s larvae. This study was aim to determine the efficacy of entomopathogenic fungi Beauveria bassiana with the mortality level of Culex quinquefasciatus larvae. This study used experiment method with a Randomized Control Trial design. The samples were the third instar larvae susceptible of Culex quinquefasciatus with a total samples of 1.475 tails from laboratorium. Powder of Beauveria bassiana was from Coffee and Cocoa Research Center Jember. Analysis with ANOVA 95% significance results showed the differences in the number of dead larvae of Culex quinquefasciatus at each concentration and time series observations used in the experiment that proved the existence of significant different mortality of Culex quinquefasciatus larvae at various levels of concentration of Beauveria bassiana and various time series observations. LC50 value at 48 hours observations was 1.932 ppm and LC90 was 16.322 ppm with 95% significance. LT50 value was 36,520 hours and LT90 was 47,682 hours with 95% significance. Increasing the concentration is directly proportional to the increase in density conidiospore. Based on this research, it is known that Beauveria bassiana as biolarvicide effective in biological control against filariasis. Suggestions to other research is can be to determine the efficacy using fungal isolates from endemic areas.